2016
DOI: 10.3389/fnut.2016.00049
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Time to Steady-state Resting Energy Expenditure Using Indirect Calorimetry in Young, Healthy Adults

Abstract: Indirect calorimetry (IC) measurements to estimate resting energy expenditure (REE) necessitate a stable measurement period or steady state (SS). There is limited evidence when assessing the time to reach SS in young, healthy adults. The aims of this prospective study are to determine the approximate time to necessary reach SS using open-circuit IC and to establish the appropriate duration of SS needed to estimate REE. One hundred young, healthy participants (54 males and 46 females; age = 20.6 ± 2.1 years; bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…For example, although the best practice guideline recommends at least 20-min rest before the RMR measurement (13) , recent studies among healthy young adults showed that a resting period before the RMR measurement could be omitted. In previous studies, during the 30-min RMR measurement, a steady state was achieved after 5 min and there was no difference in RMR between each of the 5-min segment after the first 5 min (18,19) . Therefore, in this study, a rest period prior to both the RMR measurements was not imposed in order to minimise the total duration, to create a comfortable testing environment and to mimic the practicality in clinical practice.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…For example, although the best practice guideline recommends at least 20-min rest before the RMR measurement (13) , recent studies among healthy young adults showed that a resting period before the RMR measurement could be omitted. In previous studies, during the 30-min RMR measurement, a steady state was achieved after 5 min and there was no difference in RMR between each of the 5-min segment after the first 5 min (18,19) . Therefore, in this study, a rest period prior to both the RMR measurements was not imposed in order to minimise the total duration, to create a comfortable testing environment and to mimic the practicality in clinical practice.…”
Section: Discussionmentioning
confidence: 78%
“…Comparing the percentage of participants reaching a steady state with previous studies using either QUARK RMR or Fitmate GS is not possible because the criteria for the steady state were not defined and the percentage of participants who reached the steady state was not reported (9)(10)(11)44) . Studies using a canopy hood but different metabolic monitoring devices reported that 93-95 % of healthy adults reached a steady state over five consecutive minutes within the 30 min (18,48) . Portable metabolic monitoring device 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Average Cardiac Index levels started out at 3.3 L/min/m 2 upon sitting, consistent with the CI expected of this age group when supine (4.87-0.023 × age; Katori, 1979 ), then fell by one third to below 2.2 L/min after 30 min of sitting. This long-duration continuous drop in CI is very different than that seen in young adults, where changes in resting metabolic rate (a surrogate measure of cardiac index) have been shown to plateau in 10 to 15 min ( Popp, Risch, Sakarcan, Bridges, & Jesch, 2016 ). However, these results are consistent with recent work assessing lower limb fluid pooling which show that fluid pooling in older adults (40-70 years) can progress for more than 4 hr ( Singh, Yadollahi, Lyons, Alshaer, & Bradley, 2017 ).…”
Section: Discussionmentioning
confidence: 89%
“…Subjects were asked to relax and breathe normally while sitting or standing. Subjects rested for 20 minutes before gas samples were collected to allow for a steady state to be reached [15]. During the last ten minutes of each 30-minute period each subject breathed into a meteorological balloon using a one-way valve (Hans Rudolph, Kansas City, MO).…”
Section: Preliminary Testingmentioning
confidence: 99%